Characterization of local implementations of parabolic grid antenna systems - Hombrebueno, Ben Joseph V.
This study will assess the local conditions in mass production of antenna systems. The student will implement parabolic antenna systems for the 900 MHz, 2.4 GHz and 5.8 GHz bands. Characterization of the antennas will be done and comparisons to properties of antennas available in the market will be made. Production and other costs will be computed afterwards to determine feasibility.